2021
DOI: 10.1021/acs.molpharmaceut.1c00081
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Physical Study of Three Pharmaceutically Active Benzodiazepine Derivatives: Crystalline versus Amorphous State and Crystallization Tendency

Abstract: unidimensional growth with only sporadic nucleation, which allows a direct assessment of the crystal growth rate. Despite the very similar growth mode, the two derivatives exhibit very different kinetics for a fixed value of the reduced temperature and thus of the structural relaxation time, with Nordazepam displaying slower growth kinetics. Diazepam does not instead display any tendency towards recrystallization over short periods of time (even close to T m ). Both these observations in three very similar dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 73 publications
2
16
0
Order By: Relevance
“…The inset to Figure 9 a displays representative low-temperature spectra of pure NOR. As we reported already in an earlier study [ 17 ], a secondary relaxation, labelled here as β N , is observed on the high-frequency flank of the α relaxation. Like the α process, the β N relaxation shifted to higher frequency with increasing temperature.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The inset to Figure 9 a displays representative low-temperature spectra of pure NOR. As we reported already in an earlier study [ 17 ], a secondary relaxation, labelled here as β N , is observed on the high-frequency flank of the α relaxation. Like the α process, the β N relaxation shifted to higher frequency with increasing temperature.…”
Section: Resultssupporting
confidence: 76%
“…As we discussed in a recent publication [ 17 ], in the pure drug, this relaxation corresponds to a non-diffusive relaxation of the whole molecule known as Johari–Goldstein (JG) β relaxation [ 36 , 37 ]. These secondary relaxations are observed in fully rigid molecules [ 38 , 39 , 40 ] and in polymers with monoatomic or methyl side groups such as polybutadiene and 1,4-polyisoprene [ 41 , 42 ] and correspond to rigid roto-translations of whole molecules or chain segments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the introduction, a recent X-ray diffraction study of the two crystalline forms of BrBPh has shown that the molecular structure of the brominated derivative is not helicoidal as the ground-state structure of unsubstituted BPh, but rather displays a coplanar phenyl-ketone moiety, tilted with respect to the brominated ring 45 . This molecular geometry entails the existence of two possible enantiomers with same energy and opposite chirality, and both the stable and metastable crystal phases of BrBPh are in fact racemic mixtures with equal population of both enantiomers 40 . Since the metastable crystalline phase is formed by recrystallization from supercooled liquid BrBPh, it is likely that the inter-enantiomer conversion is active in the liquid state (we cannot exclude a priori the possibility that conformers with different internal torsion angles coexist in the liquid phase).…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the origin of the secondary dielectric response of BPh and further analyze the effect of constrained internal rotation in molecules with germinal aromatic rings, in the present contribution we analyze the temperature- and pressure-dependent relaxation dynamics of a singly-substituted halogenated derivative of BPh, namely ortho-bromobenzophenone (hereafter, BrBPh), and compare the results with more detailed dielectric spectra of BPh that we have acquired near the glass transition of this compound. The comparative analysis of the molecular relaxations of closely-related molecular derivatives can indeed be a valuable tool for the identification of secondary processes 40 . We choose BrBPh because it only differs from the parent molecule by substitution of a single atom, and it has better glass-forming ability and kinetic stability of the supercooled liquid phase than pristine BPh.…”
Section: Introductionmentioning
confidence: 99%